1974
DOI: 10.1002/pssa.2210260230
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscopy study of the effects of annealing on the defect structure of heavily silicon-doped gallium arsenide

Abstract: The lattice defects in heavily silicon-doped gallium arsenide crystals grown by the horizontal Bridgman method were examined as a function of heat treatment and silicon concentration by using transmission electron microscopy. The substructure of as-grown crystals, containing =4 x l O l 9 Si/cmS exhibited the presence of numerous extrinsic stacking faults lying on t h e { 111) and small vacancy type prismatic dislocation loops lying parallel t o the { 110) planes of GaAs. Annealing these crystals at 1100 "C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…and co-workers concluded that the loop-like defects on {110} planes present in 300 keV proton bombarded (10 15 to 10 16 H + cm −2 ) n-type Si-doped GaAs annealed in the range 500 • C to 900 • C were hydrogen filled vacancy loops (called hydrogen platelets) [3][4][5] which, due to the gas pressure inside the loops, would appear to be of interstitial nature [3]. This conclusion was supported by still earlier reports of vacancy loops on {110} planes observed in Si-and Te-doped GaAs annealed at high temperatures [6][7][8] and the fact that for low dose electron irradiated n-type GaAs, pointdefect annealing already occurs in the temperature range 200 to 300 • C, which is evidence for point defect mobility in this temperature range [9]. The new data presented in this paper allows for a reinterpretation of the older defect models in proton bombarded n-type GaAs, i.e.…”
Section: Introductionsupporting
confidence: 70%
“…and co-workers concluded that the loop-like defects on {110} planes present in 300 keV proton bombarded (10 15 to 10 16 H + cm −2 ) n-type Si-doped GaAs annealed in the range 500 • C to 900 • C were hydrogen filled vacancy loops (called hydrogen platelets) [3][4][5] which, due to the gas pressure inside the loops, would appear to be of interstitial nature [3]. This conclusion was supported by still earlier reports of vacancy loops on {110} planes observed in Si-and Te-doped GaAs annealed at high temperatures [6][7][8] and the fact that for low dose electron irradiated n-type GaAs, pointdefect annealing already occurs in the temperature range 200 to 300 • C, which is evidence for point defect mobility in this temperature range [9]. The new data presented in this paper allows for a reinterpretation of the older defect models in proton bombarded n-type GaAs, i.e.…”
Section: Introductionsupporting
confidence: 70%
“…The above mentioned phenomena seem to correspond to the behaviour of GaAs doped with Si [28], Se [26,27] and S [29] as well. On the contrary, Zn doping gives neither loops nor stacking faults, even at concentrations above 1019 at.cm-3 [26,27,29].…”
Section: Microstructure Of Annealed Doped Crys-mentioning
confidence: 98%
“…In the case of Si doped GaAs [28], annealing at 1100 °C yields to a homogeneous solid solution. A further annealing at 750 °C with [Si] = 4 x 1019 at.cm-3 causes the formation of a large quantity of small loops, when at 600 and 800 °C, a small number of large loops develops.…”
Section: Microstructure Of Annealed Doped Crys-mentioning
confidence: 99%
See 1 more Smart Citation
“…Darby et al [14] attributed the triangular faulted defects in Zn-diffused Si-doped GaAs to Zn precipitation. In addition, stacking faults on the {111} planes in heavily Si-doped Bridgman-grown GaAs have been attributed to Si precipitation [20][21][22]. Although these defects have also not been reported in Si implanted GaAs [15][16][17], they have been observed in very highly Si-doped gradient freeze grown GaAs [8,18,19].…”
Section: Si Precipitates On {111} Planesmentioning
confidence: 99%